The Law Enforcement Analysis of Violations of the Notary Code of Ethics - Eva Zuliana; Umar Ma'ruf; Rakhmat Bowo Suharto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The law enforcement is an effort to implement the code of ethics of a notary as it should be, supervise its implementation so that there is no violation, and if there is a violation, restore the violated code of ethics so that it is re-enforced. Notaries in carrying out their duties and positions are not closed to the possibility of committing violations. This study aims to find out and analyze the enforcement of the code of ethics for notaries who have committed violations, and what are the obstacles to the Notary Honorary Council in imposing sanctions on the code of ethics for notaries who commit violations. Based on research results shown the law enforcement of the code of ethics for notaries who commit violations is that the Honorary Council makes summons, gives warnings to notaries who commit violations, and holds hearings to examine suspected violations of the code of ethics. The obstacles of the Notary Honorary Council in enforcing the code of ethics are the limited number of members of the Notary Honorary Council so that they cannot carry out their duties optimally if one of them cannot attend, and there is a feeling of reluctance to fellow professionals to reprimand or impose sanctions.